Are smallholder farmers better or worse off from an increase in the international price of cereals? - Nakelse, Tebila; Dalton, Timothy J.; Hendricks, Nathan P.; Hodjo, Manzamasso (My University, 2018)
The effect of agricultural price shocks on household welfare in low-income countries is a major concern for policymakers attempting to reduce poverty rates. This study estimates the impact of an increase in the world cereal price on rural households in Burkina Faso in an agricultural household model framework. We account for imperfect transmission of global prices to local prices as well as supply and demand response of rural households to price signals. The increase in price during the period from 2006 to 2014 is translated to welfare improvement ranging from 0.02 percent for 2006 to 0.06 percent for 2011 for farmers in Burkina Faso.
Citation: Nakelse, T., Dalton, T. J., Hendricks, N. P., & Hodjo, M. (2018). Are smallholder farmers better or worse off from an increase in the international price of cereals? Food Policy, 79, 213–223. https://doi.org/10.1016/j.foodpol.2018.07.006